Penatalaksanaan Asma Varian Batuk - Wicaksono, Muhammad Bimo Adi; Yunus, Faisal (Majalah Kedokteran Indonesia, 2024)
Cough is one of the innate primitive reflexes that is part of the immune system to protect the body from foreign substances. Cough is a manifestation of symptom found in various lung diseases, both infectious and non-infectious lung diseases. Cough variant asthma is a phenotype of asthma with the only symptom of cough. In cough variant asthma, airway (bronchial) hyperresponsiveness is found without abnormalities in pulmonary function tests. Airway hyperresponsiveness is assessed from the bronchial provocation test by measuring provocation dose (PD20) or provocation concentration (PC20). Management of cough variant asthma is no different from classic asthma, which are inhalation of bronchodilators and corticosteroids. Partial response to inhalation therapy can be reversed by changing the treatment regimen, increasing the inhaled dose, or adding other drugs such as long-acting β2 agonists, sustained-release theophylline or leukotriene receptor antagonist (LTRA).